Atmospheric Determinants of Feed, Fodder, and Forage Contamination in a Changing Climate: Emerging Challenges for Sustainable Livestock Production - Md. Emran Hossain (International Journal of Atmosphere, 2026)
Feed, fodder, and forage contamination represents a growing constraint to sustainable livestock production under a changing climate. Atmospheric determinants such as rising temperature, altered precipitation patterns, increased humidity, elevated carbon dioxide concentration, and enhanced aerosol and pollutant loads are increasingly recognized as critical drivers of contamination risks across feed supply chains. These atmospheric factors directly and indirectly influence crop growth, fungal proliferation, mycotoxin biosynthesis, microbial survival, and the deposition of airborne chemical and physical contaminants on forage resources. Climate driven variability further intensifies contamination during pre-harvest, harvest, and post-harvest stages by modifying drying efficiency, storage stability, and pest and pathogen dynamics. This review synthesizes current knowledge on the role of atmospheric determinants in shaping contamination pathways in feed, fodder, and forage systems, with particular emphasis on mycotoxins, airborne pollutants, and climate sensitive biological hazards. The consequences of contaminated feed on livestock health, productivity, reproductive efficiency, and product safety are critically examined, highlighting implications for food security and public health. Advances in detection, monitoring, and climate linked risk assessment tools are discussed, alongside mitigation and adaptation strategies including climate smart agronomic practices, improved storage management, and integrated policy approaches. Key knowledge gaps are identified, especially regarding region specific risks, predictive modeling, and the integration of atmospheric data into feed safety frameworks. The review concludes that addressing atmospheric determinants of feed contamination is essential for building resilient livestock systems and ensuring sustainable animal production under future climate scenarios.
Keywords: Airborne pollutants; Climate change; feed contamination; forage safety; livestock productivity; mycotoxins; sustainable production